Development of a new process for palm oil refining based on supercritical fluid extraction technology - Abdul Manan, Zainuddin; Lim, Chee Siang; Sarmidi, Mohd. Roji (2005)

(untitled)
This work described the development of a new flowsheet model for palm oil refining using supercritical fluid extraction (SFE) technology. The first step was the synthesis of a new flowsheet structure to recover high purity palm oil which includes its minor components. Next, a thermodynamic model was developed to predict the phase equilibrium behavior of the crude palm oil (CPO)-supercritical CO2 mixture. The process structure to recover high nutritional value oil using supercritical fluid was finally simulated by means of the commercial process simulation package Aspen PLUSÂ® release 10.2.1 based on the Redlich-Kwong-Aspen (RKA) thermodynamic model. The results obtained were in good agreement with the pilot plant data reported in the literature. It is envisioned that the development of the new, intensified and simpler palm oil refining process that is based on SFE technology can overcome the limitations of the existing technology for palm oil refining apart from making the refining process drastically simpler.